COVID-19 Pandemic as a Mediator of Online Commerce Development - E. A. Konnikov; D. G. Rodionov (Управленческое консультирование)
The relevance of this study is determined by its specificity — the recent coronavirus pandemic that has affected all areas of activity, including the e-commerce market. Subjects from the top-40 countries in terms of COVID-19 infection rates were selected for analysis, including both developed countries and countries with transitional economies. The research aims to mathematically detail the influence of the coronavirus and its consequences on the ecommerce market. The study identified key factors that determined the size of the online market and described key development trends. The research considered two conceptual models, the first of which relates to the pre-pandemic period in 2019, while the second model reflects the situation after the pandemic and examines the year 2021. Factors of primary importance, such as ICT level, HDI index, average population age, number of internet users in the country, GDP, inflation, support for small business in the country, globalization index, press freedom index, and the presence of international agenda in the country’s news, were selected as first-order factors. According to the forecast, the growth rates of the online trading market will consistently remain at a high level and will not return to pre-pandemic levels. By understanding the impact of the coronavirus on the e-commerce market, market participants can adjust their development strategy for more effective response to changing market conditions.